Using a Systematic Approach to Teach Analysis of the Aging Face. Issue 3 (July 2021) - Sivam, Sunthosh; Kim, Patrick; Humphrey, Clinton; Kriet, J. David
Objective: To assess the efficacy of a novel systematic approach aimed at improving a resident physician's ability to perform analysis of the aging face. Study Design: Prospective randomized case-control study. Setting: Accreditation Council for Graduate Medical Education accredited Otolaryngology–Head and Neck Surgery residency program. Methods: Twenty otolaryngology–head and neck surgery residents were randomized into 2 groups with even representation in each postgraduate year level in each cohort. One group used traditional materials (textbooks), and the other group was given exclusive access to the online learning module featuring a systematic approach to aging-face analysis. Both groups completed preactivity, postactivity, and retention assessments to gauge their ability to perform a comprehensive analysis of the aging face. Results: When compared with a matched control cohort, the residents who used the systematic approach performed more comprehensive facial aging assessments immediately after the intervention and at a retention time point. Conclusion: A systematic approach delivered via an 11-minute online module can significantly improve a resident physician's ability to perform analysis of the aging face. This systematic approach could be easily integrated into other online or traditional educational curriculums. Moreover, this methodology could be applied to additional areas in which residents have limited exposure but must develop expertise.